Analisis Penerapan Pendidikan Karakter Masa Pembelajaran Pandemic Covid-19 Di SD N 157 Laerung Kabupaten Wajo - Muhammad Amran; Besse Rahmawati; Sudirman Sudirman (STKIP Andi Matappa Pangkep, 2022)
The problem in this study is that many graduates have a high level of knowledge, but the level of personality/character is still low, then the emergence of Covid-19 which resulted in a change in the learning system from face to face to online. This study is a qualitative descriptive study that aims to describe how to apply character education during the Covid-19 pandemic learning period. The results showed that the character values developed during the Covid-19 pandemic learning period were the five main values for Strengthening Character Education (PPK), namely religious, nationalist, independent, mutual cooperation and integrity values. example, discussion/question and answer and role playing. Obstacles in instilling character values in students from the facilities and limited learning time, then the collaboration between teachers and parents in inculcating student character values during pandemic learning. In conclusion, the implementation of character education at SDN 157 Laerung is good with the application of the five main values of Penguatan Character Education (PPK), so that the character values shown by students include religious, nationalist, independent, mutual cooperation and integrity values by instilling character values. through habituation and giving examples, discussion/question and answer and role playing.